Analysis of the Effectiveness of Painting Art Healing in Mental Health Problems in Different Populations - Kuang, Xinyue (International Journal of Social Sciences and Public Administration, 2024)
This study aims to systematically analyze the application effect of painting therapy in the treatment of mental health problems in different populations, and to explore its universality and specificity in different age groups, genders, cultural backgrounds, and mental health conditions. Through literature review, comparative research methods, and case study methods, the effectiveness of art therapy in elderly, adult, adolescent, and child populations was comprehensively evaluated. The results of the study show that art therapy can significantly promote emotional regulation, improve cognitive function, enhance social interaction, and develop self-identity, especially in alleviating emotional disorders such as anxiety and depression. However, this study also found that there are certain deficiencies in the methodological quality, sample representativeness, and long-term effects research of art therapy. Future research should further focus on the standardization, long-term effectiveness, and cross-cultural applicability of interventions to promote the widespread application of art therapy in the field of mental health.